2023
DOI: 10.3389/fmicb.2023.1123448
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics study and ncRNA regulation of anti-BmNPV in silkworms, Bombyx mori: an update

Yi-Xuan Fan,
Vivian Andoh,
Liang Chen

Abstract: Bombyx mori silkworm is an important economic insect which has a significant contribution to the improvement of the economy. Bombyx mori nucleopolyhedrovirus (BmNPV) is a vitally significant purulent virus that impedes the sustainable and stable development of the silkworm industry, resulting in substantial economic losses. In recent years, with the development of biotechnology, transcriptomics, proteomics, metabolomics, and the related techniques have been used to select BmNPV-resistant genes, proteins, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
1
1
0
Order By: Relevance
“…Following the A. apis infection, 386, 351, and 272 DElncRNAs were detected in the 4-, 5-, and 6-day-old comparison groups, respectively, indicative of the alteration of the overall expression pattern of host lncRNAs caused by fungal invasion. This is similar to findings from other insects, such as Sarcophaga peregrina , Aedes aegypti , and B. mori in response to various pathogens or parasites [ 32 , 33 , 34 ]. In addition, 30 DElncRNAs (MSTRG.…”
Section: Discussionsupporting
confidence: 87%
“…Following the A. apis infection, 386, 351, and 272 DElncRNAs were detected in the 4-, 5-, and 6-day-old comparison groups, respectively, indicative of the alteration of the overall expression pattern of host lncRNAs caused by fungal invasion. This is similar to findings from other insects, such as Sarcophaga peregrina , Aedes aegypti , and B. mori in response to various pathogens or parasites [ 32 , 33 , 34 ]. In addition, 30 DElncRNAs (MSTRG.…”
Section: Discussionsupporting
confidence: 87%
“…MiRNAs have been discovered to be involved in the resistance to viral invasion and replication in B. mori (Awais et al, 2021;Fan et al, 2023) and other species, such as S. frugiperda , Epinephelus coioides (Li et al, 2021) and Litopenaeus vannamei (Bao et al, 2020) and so on. In our previous study, we identified that miR-6498-5p was one of the differentially expressed miRNAs in B. mori upon BmNPV infection (Cao et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have demonstrated that circRNAs exert regulatory functions in diverse aspects of vertebrates such as growth, development, metabolism, and immunity through cis-acting effect [50][51][52][53]. For instance, Weigelt et al [51] previously detected the continuous up-regulation of the circRNA transcribed from the sulfateless gene (circSfl) in the brain and muscle of insulin mutant flies, and the circSfl overexpression prolonged the host lifespan.…”
Section: Discussionmentioning
confidence: 99%